El hombre culto: una aproximación a la Historia de la Cultura Griega, de Jacob Burckhardt / The Cultured Man: An Approach to Jacob Burckhardt’s History of Greek Culture - Pereira Caldas, Pedro Spinola (Historiografías, 2018)
Este artículo pretende investigar el sentido de la Bildung (formación) en la obra de Jacob Burckhardt. Para ello utilizará sus reflexiones teóricas (Über das Studium der Geschichte), así como sus obras sobre la cultura griega antigua (la Historia de la Cultura Griega), como principal fuente de investigación. De este modo, el objetivo del artículo será examinar la siguiente paradoja en la obra de Burckhardt: si bien ésta es heredera de la tradición de la Bildung, el historiador suizo ya apunta en ella, aunque de modo latente, los límites del ideal del hombre culto Palabras Clave Jacob Burckhardt, Bildung, cultura griega Abstract This article is intended to examine the meaning of the Bildung (formation) in the works of Jacob Burckhardt. To this purpose, it is to use his theoretical reflections (Über das Studium der Geschichte), as well his works on the ancient Greek culture (the History of the Greek Culture), as main source of inquiry. Therefore, the objective of the article is to discuss the following paradox in Burckhardt’s work: however he might be considered as an inheritor of the Bildung tradition, the Swiss historian already shows, albeit in a latent way, the limits of the ideal of cultivated man Keywords Jacob Burckhardt, Bildung, Greek Culture